«Social order» as the mechanism of political positioning of big business - A. V. Kapkina (Путеводитель предпринимателя)
The article presents an analysis of social order, which is considered to be a mechanism of political participation of big business and solution of social problems. The main causes of business interest in obtaining social orders and key forms of its implementation (public-private partnership (PPP), target programs) are described in article.